TCR signalling network organization at the immunological synapses of murine regulatory T cells. Issue 12 (12th September 2017) - van Ham, Marco; Teich, René; Philipsen, Lars; Niemz, Jana; Amsberg, Nicole; Wissing, Josef; Nimtz, Manfred; Gröbe, Lothar; Kliche, Stefanie; Thiel, Nadine; Klawonn, Frank; Hubo, Mario; et al.
Abstract: Regulatory T (Treg) cells require T‐cell receptor (TCR) signalling to exert their immunosuppressive activity, but the precise organization of the TCR signalling network compared to conventional T (Tconv) cells remains elusive. By using accurate mass spectrometry and multi‐epitope ligand cartography (MELC) we characterized TCR signalling and recruitment of TCR signalling components to the immunological synapse (IS) in Treg cells and Tconv cells. With the exception of Themis which we detected in lower amounts in Treg cells, other major TCR signalling components were found equally abundant, however, their phosphorylation‐status notably discriminates Treg cells from Tconv cells. Overall, this study identified 121 Treg cell‐specific phosphorylations. Short‐term triggering of T cell subsets via CD3 and CD28 widely harmonized these variations with the exception of eleven TCR signalling components that mainly regulate cytoskeleton dynamics and molecular transport. Accordingly, conjugation with B cells indeed caused variant cellular morphology and revealed a Treg cell‐specific recruitment of TCR signalling components such as PKCθ, PLCγ1 and ZAP70 as well as B cell‐derived CD86 into the IS. Together, results from this study support the existence of a Treg cell‐specific IS and suggest Treg cell‐specific cytoskeleton dynamics as a novel determinant for the unique functional properties of Treg cells. Abstract : Using proteomics, phosphoproteomics and MELC analyses we comparatively analysed the molecular inventory, TCR responses and dynamic distribution of TCR signalling components in Treg cells and Tconv cells. Treg cells show a pre‐activated phenotype, a unique activation response of cytoskeleton‐associated proteins and a unique immunological synapse assembly.